Returning to Political Parties? (Presses de l'Ifpo, 2010)
Are Arab parties facing a predicament? Are they paying the price of repression and limited pluralism? Have they become obsolete to the benefit of other political groups and mobilization modes such as communities, tribes, "asabiyyat" or to the disadvantage of non governmental organizations, associations and social movements? While some predicted "the end of parties" in the region as a result of authoritarian political systems, doesn't the recent transition from the one party rule towards a fra...